In-Situ Measurement of Vanadium Crossover for the Vanadium Redox Flow Battery. Issue 16 (4th December 2019) - Lagarteira, Tiago; Pacheco, Pedro; Almeida, Carlos; Bentien, Anders; Monteiro, Ricardo; Mendes, Adélio
Abstract : A simple in-situ method for the quantification of the crossover in redox flow batteries, adapted from an electrochemical method currently used for quantifying the hydrogen crossover in fuel cells, is proposed and used for characterizing a vanadium redox flow battery. A linear sweep voltammetry (LSV) scan is performed with the pertinent redox species in one side of the electrochemical cell, while in the other side is the supporting electrolyte. The LSV plot should display a plateau where the current is limited by the crossover of the selected species. The crossover results were compared with an external analytical method using MP-AES, showing very good agreement with a maximum relative difference of 6%. This method was used to quantify the crossover of all vanadium species using both cation and anion exchange membranes. The proposed method can be applied for assisting the development and characterization of ion-exchange membranes for redox flow batteries and for in-situ diagnosis of component degradation and failure in RFB systems without disassembling them.